(untitled) (Bangladesh Journal of Agricultural Research, 2018)
An intercrop-based experiment was conducted for two consecutive years during September 2012 to October 2014 at farmer’s field of MLT site, Shibganj, Bogra to find out the performance of banana intercropped with potato and vegetables. There were three intercrop-based treatments i.e. Banana + Potato, Banana + Radish + Potato and Banana + Cauliflower + Potato were tested along with Sole Banana. The results revealed that all the intercrops produced higher banana equivalent yield over the sole banana in both the years. However, among the intercrop combinations, Banana + Cauliflower + Potato provided the highest equivalent yield (104.04 tha-1 in 2012-13 and 122.50 tha-1 in 2013-14) followed by Banana + Radish + potato. Sole banana produced the lowest equivalent yield in both the cropping seasons. Higher gross margin was also obtained from the intercrop combinations. Among the intercrops, Banana + cauliflower + Potato provided higher gross margin (Tk.656898 ha-1) but due to higher cost, this treatment failed to show higher BCR than Banana + Radish + Potato. Bangladesh J. Agril. Res. 42(4): 749-755, December 2017